Application of Online Mode Professional Development in Enhancing Pedagogical and Professional Competencies in Early Grade Primary School Teacher - Syahruddin; Ahdan; Ernawati (JPP (Jurnal Pendidikan dan Pembelajaran), 2019)
The purpose of this study is to explain the online mode of professional development  application in improving teacher competency of learners. The competencies intended in this study are pedagogic competence and professional competence. The research design was carried out in quantitative and qualitative forms. The number of research samples is 30 people. Data collection method used is online media validiation and performance tests. Data analysis used descriptive statistics. The results showed validation in the online mode of continuing professional development of the learning teacher had an average value of total validity = 3.5. Thus, this value is included in the category "Very Valid" (3,5 <   < 4,0). Thus, online learning media teachers are declared to meet the validity criteria. Then there are four online modal coaching categories, namely (a) Knowing online features, (b) Writing down learning features, (c) Writing out the names of activities, and (d) Describing the use of features in each learning activity.